School as a Place of Formation of Moral-Ethical and Religious Competences - Dariusz Stępkowski (Nicolaus Copernicus University in Toruń, 2016)
A quarter-century ago, religion as a school subject was reintroduced to Polish public schools. Simultaneously, ethics lessons were organized as an alternative to religion ones. However, the problem if the formation of students' competences in these fields is a responsibility of education system remains unresolved. The article aims to deal with this case. The discussion is divided into three chapters. In the first one, the locus pedagogicus of school is defined as an "artificial" place of teaching and studying. The second one deals with a need to determine the scope of the school curriculum. In the third one, the inner logic of ethics and religion lessons is discussed, with reference to the models of moral-ethical competences and religious competences, which were elaborated by German pedagogues and can be used as far as Polish public education system is concerned.